Pengalaman Perawat dalam Melaksanakan Model Penugasan Tim pada Masa Covid - 19 di Rumah Sakit - Miftahul Khoiriyah Siregar; Dudut Tanjung; Rika Endah Nurhidayah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to explore in depth the experiences of nurses in carrying out the team assignment model during the COVID-19 period at the hospital. The data collection method used qualitative research by conducting in-depth interviews with nurses at the hospital. The results of this study indicate that there are 4 themes obtained, namely as follows: 1) implementation of the team assignment model during the COVID-19 period, 2) psychological responses during implementing the team assignment model during the COVID-19 period, 3) obstacles to implementing the team assignment model during the COVID-19 period. COVID-19, 4) hope after implementing the team assignment model during the COVID-19 period. In conclusion, there were 4 themes that participants perceived related to the experience of nurses in carrying out the team assignment model during the COVID-19 period at the hospital. Keywords: COVID-19, Team Assignment Model, Nurses